Law, ideology and discourse (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper aims to examine the relationship between law, ideology and discourse. To do this, the sociocognitive theory of Teun van Dijk’s ideology is ascribed together with Joseph Raz’s institutional approach to the nature of law by exploring the possibility of existence of legal ideologies. Starting from an example, we show the overlap between the political field with the field of justice and conclude that judges adhere to at least two ideological groups, one of a political nature and the other of a professional nature.
Keywords: Ideology; Ideological groups; Ideology of judges; Sentence text